Method for producing positive electrode active material for nonaqueous electrolyte secondary battery
By continuously flowing mixed powder during the burning process, the ratio of the ratio of lithium to other elements is adjusted, and the problem of the quality of orthopedic activity materials in existing technology has been solved, and the characteristic of the excellent battery characteristic positive active material is achieved.
Patent Information
- Application Number
- CN202380046690.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-15
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, when heat treatment of mixed powders is performed using conventional rotary kilns, sufficient calcination cannot be achieved, resulting in a decrease in the quality of the positive electrode active material.
By continuously flowing mixed powder during the burning process, the ratio of the ratio of lithium to other elements is adjusted to ensure that the ratio of the ratio of the amount of lithium to the total amount of the element ME is 1.5%or smaller to achieve uniform thermal conductivity and burning.
With good production efficiency, the production of positive active materials that can give non -hydrolytic secondary battery characteristics without quality reduction.
Smart Images

Figure BDA0005184559650000111 
Figure BDA0005184559650000301 
Figure BDA0005184559650000311
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a positive electrode active material for a nonaqueous electrolyte secondary battery, by which a positive electrode active material capable of imparting excellent battery characteristics to a nonaqueous electrolyte secondary battery can be manufactured with good production efficiency without any quality degradation. Background Art
[0002] Nonaqueous electrolyte secondary batteries are compact, lightweight and have high energy density, and are well known as power sources for driving cellular phones and notebook personal computers, etc. Among these, widely used are lithium ion secondary batteries having large charge / discharge capacity and using a lithium nickelate material in the positive electrode.
[0003] Has basic composition: Li(NiM)O 2 A positive electrode active material of (wherein M is, for example, an element containing a transition metal) is used as, for example, a positive electrode active material of a lithium ion secondary battery, and such a positive electrode material is generally obtained by calcining a mixed powder containing a transition metal-containing precursor compound and a lithium compound.
[0004] As described in Patent Document 1, for example, when calcining a mixed powder, the mixed powder can be filled in a calcining container such as a sagger or a crucible, conditions such as temperature and time can be appropriately adjusted in a calcining furnace such as an electric furnace or a roller kiln, and calcination can be performed multiple times as needed, but efforts are being made to use an apparatus capable of performing heat treatment while fluidizing the material to be treated, such as an externally heated rotary kiln, because such an apparatus has higher heat conduction to the material to be treated and is more efficient than the calcining furnace mentioned above.
[0005] A conventional rotary kiln is an apparatus for pyrolyzing or carbonizing waste, etc. in a waste pyrolysis gasification and melting device or a waste carbonization device, as described in Patent Document 2, for example, in which waste (material to be processed) stably supplied into an inner cylinder of a kiln main body is fluidized while being lifted and stirred by means of a lifter (lifting blades), and the waste can be heat-treated by indirect heating using hot air which is supplied from the outside and circulated through a heating flow path.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: WO 2019 / 194150 A1
[0009] Patent document 2: JP 4670861 B2 Summary of the invention
[0010] Problems to be solved by the present invention
[0011] For example, when a single waste powder or the like is heat-treated using an apparatus such as a conventional rotary kiln, as disclosed in Patent Document 2, the effect of high heat conduction is indeed exhibited, and the intended waste pyrolysis or carbonization can be achieved.
[0012] However, as mentioned above, the positive electrode active material for lithium ion secondary batteries is produced by calcining a mixed powder containing a precursor compound and a lithium compound rather than a single powder, and when such a mixed powder is supplied to a device such as a conventional rotary kiln and subjected to heat treatment, the mixed powder separates when fluidized by simple lifting and stirring provided by lifting blades, and sufficient calcination of the mixed powder cannot be achieved, so there is a problem in the reduced quality of the resulting positive electrode active material. In addition, for example, when such a mixed powder is supplied to a device such as a rotary kiln that is set to a reduced lifting amount and does not have lifting blades installed for heat treatment, even if the mixed powder is fluidized, heat cannot be uniformly and efficiently conducted from the inner cylindrical surface (furnace wall) of the kiln body to the entire mixed powder, so there is a problem that the mixed powder cannot be uniformly calcined, resulting in an expected reduction in the quality of the positive electrode active material.
[0013] The present invention takes into account the problems in the prior art as described above, and its purpose is to provide a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, by which a positive electrode active material that can impart excellent battery characteristics to a non-aqueous electrolyte secondary battery without any quality degradation can be manufactured with good production efficiency.
[0014] Means used to solve problems
[0015] To achieve this object, the method for producing a positive electrode active material of the present invention is achieved by making adjustments to reduce changes in the ratio of lithium to other elements in calcined materials, which are continuously obtained by calcining a mixture of a precursor compound containing a transition metal and a lithium compound while fluidizing it.
[0016] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention (method A) comprises at least the following steps in order:
[0017] (1) Step (1), wherein at least a positive electrode active material precursor compound and a lithium compound are mixed to prepare a powdery mixture; and
[0018] (2) step (2), wherein the powdery mixture obtained in step (1) is calcined to produce a calcined material,
[0019] wherein the precursor compound is a composite compound containing oxygen (O) and at least one element (Me) other than lithium (Li) and oxygen (O), and
[0020] wherein in step (2), the calcined material is produced while the powdered mixture is continuously fluidized at least from the start until the end of calcination, so that for the calcined materials obtained at all predetermined elapsed times, the coefficient of variation of the ratio (Li / Me) of the amount of lithium (Li) to the total amount of the element (Me) in the calcined material obtained at a predetermined elapsed time is 1.5% or less.
[0021] Another embodiment of the present invention relates to a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery (method B), the method comprising at least the following steps in sequence:
[0022] (1) Step (1), wherein at least a positive electrode active material precursor compound and a lithium compound are mixed to prepare a powdery mixture; and
[0023] (2) step (2), wherein the powdery mixture obtained in step (1) is calcined to produce a calcined material,
[0024] wherein the precursor compound is a composite compound containing oxygen (O) and at least one element (Me) other than lithium (Li) and oxygen (O), and
[0025] wherein in step (2), the calcined material is produced while the powdered mixture is continuously fluidized at least from the beginning to the end of calcination; wherein step (2) is carried out in a rotary kiln in which one or more lifting blades are arranged on a surface portion inside the furnace core tube.
[0026] Advantageously, method B is carried out in such a manner that, for the calcined materials obtained at all predetermined elapsed times, the coefficient of variation of the ratio (Li / Me) of the amount of lithium (Li) to the total amount of element (Me) in the calcined material obtained at a predetermined elapsed time is 1.5% or less.
[0027] For the purposes of the present invention, calcining means subjecting the material to a thermal (=heat) treatment (sometimes also called firing), for example in a temperature range of 350° C. to 1000° C. A calcined (fired) material is thus a material which has been subjected to a thermal treatment (firing).
[0028] For the purposes of the present invention, fluidizing means causing a material to flow independently of its physical state, ie independently of whether it is in a solid state, or partially or completely molten.
[0029] Advantages of the present invention
[0030] The present invention makes it possible to provide methods by which a positive electrode active material capable of imparting excellent battery characteristics to a nonaqueous electrolyte secondary battery can be produced with good production efficiency without any deterioration in quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] [ Figure 1 ] is a schematic cross-sectional view in the radial direction of an example of a furnace core tube of a rotary kiln in which lifting blades are arranged on a surface portion inside the furnace core tube, which furnace core tube can be used in an embodiment of the method of the present invention for producing positive electrode active materials for non-aqueous electrolyte secondary batteries according to the present invention.
[0032] [Figure 2] is a schematic cross-sectional view in the radial direction of a furnace tube of a rotary kiln, in which lifting blades are arranged on a surface portion inside the furnace tube so as to show the lifting height of a powdered mixture during lifting and stirring using a rotary kiln, which is an example of lifting and stirring in a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention, wherein (a) is a schematic cross-sectional view in the radial direction of the furnace tube, in which the lifting blades are installed at an angle of 45° on the surface portion, and (b) is a schematic cross-sectional view in the radial direction of the furnace tube, in which the lifting blades are installed at an angle of 60° on the surface portion.
[0033] [Figure 3] is a schematic cross-sectional view in the radial direction of the furnace core tube of the rotary kiln used in Examples 1-1 to 1-3 and Examples 2-1 to 2-3, wherein (a) is a schematic cross-sectional view in the radial direction of the furnace core tube, in which the installation angle of the lifting blade on the surface portion is 30°, (b) is a schematic cross-sectional view in the radial direction of the furnace core tube, in which the installation angle of the lifting blade on the surface portion is 45°; and (c) is a schematic cross-sectional view in the radial direction of the furnace core tube, in which the installation angle of the lifting blade on the surface portion is 60°. DETAILED DESCRIPTION
[0034] Embodiments of the present invention will be described below. The following description of the preferred embodiments is given essentially by way of example only and is not intended to limit the present invention, its application methods or its uses. Unless otherwise specified, the following applies to both method A and method B.
[0035] Preferably, the mixed powder containing at least a precursor compound and a lithium compound is calcined in fluidization rather than at rest, so as to produce a positive electrode active material for a non-aqueous electrolyte secondary battery with high heat conduction and higher efficiency. However, when a mixed powder such as this is calcined while fluidized rather than a single powder, simple lifting and stirring cause the mixed powder to separate and cannot achieve sufficient calcination, so the quality of the resulting positive electrode active material is reduced. In addition, if the lifting amount of the mixed powder is reduced, the heat cannot be uniformly and efficiently conducted to the entire mixed powder, so uniform calcination cannot be achieved, resulting in an expected reduction in the quality of the positive electrode active material.
[0036] In view of these problems, it is understood that when a mixed powder comprising a precursor compound and a lithium compound is calcined, it is important to fluidize the mixed powder so as to achieve high heat conduction while suppressing separation of the mixed powder. Suppressing separation of the mixed powder means suppressing changes in the composition of the calcined material caused by separation of the mixture, that is, suppressing changes in the ratio (Li / Me) of lithium (Li) to elements (Me) other than lithium and oxygen in the calcined material.
[0037] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention comprises at least the following steps in sequence:
[0038] (1) a step of mixing at least a positive electrode active material precursor compound and a lithium compound to prepare a powdery mixture; and
[0039] (2) A step of calcining the powdery mixture obtained in step (1) to produce a calcined material. These steps will be described in order below.
[0040] <Step (1)>
[0041] The positive electrode active material precursor compound used to prepare the powdery mixture in step (1) is a composite compound containing oxygen (O) and at least one element (Me) other than lithium (Li) and O, examples of which include: composite hydroxides, composite oxides obtained by calcining composite hydroxides, and composite carbonates, which contain the element Me and are synthesized by ordinary methods.
[0042] There is no particular limitation on the element Me, which is an element capable of constituting a positive electrode active material and should be appropriately selected according to the intended composition of the positive electrode active material, but examples that can be cited include: nickel (Ni), cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), niobium (Nb), tungsten (W), molybdenum (Mo), vanadium (V), chromium (Cr), calcium (Ca), iron (Fe), gallium (Ga), strontium (Sr), yttrium (Y), ruthenium (Ru), indium (In), tin (Sn), tantalum (Ta), bismuth (Bi), zirconium (Zr), boron (B) and phosphorus (P), etc. Preferably, Me includes at least one of the following: nickel (Ni), cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), niobium (Nb), tungsten (W), molybdenum (Mo), vanadium (V), chromium (Cr), calcium (Ca), iron (Fe), gallium (Ga), strontium (Sr), yttrium (Y), ruthenium (Ru), indium (In), tin (Sn), tantalum (Ta), bismuth (Bi), zirconium (Zr), boron (B) and / or phosphorus (P); and more preferably includes at least one of the following: nickel (Ni), cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), niobium (Nb), or tungsten (W). Even more preferably, Me includes at least Ni, and specifically includes Ni and at least one of Co, Al and Mn. Specifically, Me includes Ni, Co and one or two of Al and Mn.
[0043] Preferably, the precursor compound comprising oxygen (O) and at least one element (Me) is a composite hydroxide, a composite oxide, a composite carbonate or its mixed form. "Mixed form" means that the precursor compound includes two or more of hydroxide, oxide and carbonate. By way of example only, if oxide is to be prepared by corresponding hydroxide and conversion is incomplete, mixed hydroxide / oxide forms may be produced from the preparation process. If the precursor compound is a composite hydroxide, a composite oxide, a composite carbonate or its mixed form, Me preferably includes (in addition) one or more of the metals or semimetals listed above. Specifically, the precursor compound is a hydroxide, an oxide or its mixed form.
[0044] For example, a composite hydroxide, composite oxide, composite carbonate or the like containing at least Ni is preferable as the precursor compound, and a composite hydroxide, composite oxide, composite carbonate or the like containing at least Ni, Co and Al and / or Mn is more preferable.
[0045] There is no particular limitation on the method for synthesizing the precursor compound, and by way of example, the following method can be adopted, namely, preparing at least one type of aqueous solution of at least one type of element Me or its compound according to the composition of the intended positive electrode active material; adjusting the blending ratio as needed; adding the material dropwise into a stirred retort, wherein, for example, one or more types of alkaline aqueous solutions such as sodium hydroxide aqueous solution and ammonia solution serve as mother liquors; and co-precipitating these materials by means of a controlled crystallization reaction, while also adding sodium hydroxide or the like so that the pH is within a suitable range of, for example, about 11 to about 13, thereby obtaining a hydroxide, oxide, or carbonate or the like having a shape in which primary particles agglomerate to form secondary particles.
[0046] The compound of the element Me is not particularly limited, but examples thereof include nickel compounds, cobalt compounds, manganese compounds, magnesium compounds, aluminum compounds, titanium compounds, zinc compounds, niobium compounds, tungsten compounds, and the like.
[0047] There are no particular limitations on the nickel compound, but examples thereof include nickel sulfate, nickel oxide, nickel hydroxide, nickel nitrate, nickel carbonate, nickel chloride, nickel iodide, and metallic nickel.
[0048] There are no particular limitations on the cobalt compound, but examples thereof include cobalt sulfate, cobalt oxide, cobalt hydroxide, cobalt nitrate, cobalt carbonate, cobalt chloride, cobalt iodide, and metallic cobalt.
[0049] The manganese compound is not particularly limited, but examples thereof include manganese sulfate, manganese oxide, manganese hydroxide, manganese nitrate, manganese carbonate, manganese chloride, manganese iodide, metallic manganese and the like.
[0050] The magnesium compound is not particularly limited, but examples thereof include magnesium sulfate, magnesium oxide, magnesium hydroxide, magnesium nitrate, magnesium carbonate, magnesium chloride, magnesium iodide, and metallic magnesium.
[0051] There are no particular limitations on the aluminum compound, but examples thereof include aluminum sulfate, aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum carbonate, aluminum chloride, aluminum iodide, sodium aluminate, and metallic aluminum.
[0052] The titanium compound is not particularly limited, but examples thereof include titanyl sulfate, titanium oxide, titanium hydroxide, titanium nitrate, titanium carbonate, titanium chloride, titanium iodide, metallic titanium, and the like.
[0053] There are no particular limitations on the zinc compound, but examples thereof include zinc sulfate, zinc oxide, zinc hydroxide, zinc nitrate, zinc carbonate, zinc chloride, zinc iodide, metallic zinc, and the like.
[0054] There are no particular limitations on the niobium compound, but examples thereof include niobium oxide, niobium chloride, lithium niobate, niobium iodide and the like.
[0055] There are no particular limitations on the tungsten compound, but examples that may be cited include tungsten oxide, sodium tungstate, ammonium paratungstate, tungsten hexacarbonyl, and tungsten sulfide.
[0056] While taking into account the composition of the intended positive electrode active material, the type and blending ratio of the compound of the element Me should be appropriately adjusted so that each element is of a desired type and in a desired ratio.
[0057] In addition, the precursor compound obtained by means of the wet reaction as described above can be subjected to a washing treatment and a drying treatment after dehydration. By carrying out the washing treatment, impurities in the form of sulfate and carbonate, and Na parts that are brought into the agglomerated particles and adhered to the surface layer during the reaction can be washed away. In addition, the drying treatment can be carried out at, for example, between about 50° C. and about 250° C. under an oxidizing atmosphere or the like.
[0058] In addition, the precursor compound can also be subjected to oxidation treatment under an oxidizing atmosphere at, for example, between about 300° C. and about 800° C. The oxidation treatment oxidizes the precursor compound, while impurities are also separated from the precursor compound, and the purity of the precursor compound can also be improved. In addition, the packing density can also be increased, and the production efficiency can be improved.
[0059] The particle size of the precursor compound is not critical. However, in a particular embodiment, it is in the range of 1 to 30 μm. Within this range, the particle size can be determined by conventional means, for example using electron micrographs (SEM photographs), in particular SEM photography as defined below. In the case of spherical particles, the particle size refers to the diameter, and in the case of non-spherical particles, the particle size refers to the maximum dimension.
[0060] The precursor compound synthesized in the above manner is then mixed with a lithium compound at a predetermined ratio to prepare a powdered mixture. The method of mixing the precursor compound with the lithium compound can adopt, for example, the following method, in which the precursor compound powder and the lithium compound powder are weighed out at a predetermined ratio, and dry mixed using, for example, a mixing and stirring machine, etc. In addition, while taking into account the composition of the expected positive electrode active material, the blending ratio of the precursor compound and the lithium compound should be appropriately adjusted so that the amount of Li and the total amount of the element Me reach a desired ratio.
[0061] There is no particular limitation on the lithium compound to be mixed with the precursor compound, and various types of lithium salts can be used. Examples of lithium compounds that can be cited include lithium carbonate, lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium nitrate, lithium acetate, lithium bromide, lithium chloride, lithium citrate, lithium fluoride, lithium iodide, lithium lactate, lithium oxalate, lithium phosphate, lithium pyruvate, lithium sulfate, and lithium oxide, etc. Lithium carbonate, lithium hydroxide monohydrate, and anhydrous lithium hydroxide are preferred as lithium compounds.
[0062] The particle size of the lithium compound is not critical. By way of example only, in a particular embodiment, it may be in the range of 1 μm to 10 mm. Within this range, the particle size may be determined by conventional means, such as using electron micrographs (SEM photographs), in particular using SEM photography as defined below in the μm range, and using visual inspection or optical microscopy in the range of 500 μm to 10 mm.
[0063] In addition, a compound of an element used as an additive may be added as needed. Such a compound may also be added when the precursor compound is mixed with the lithium compound, and the method of addition that can be cited includes adding in powder form or spraying in solution form. It should be noted that there is no particular limitation on the element compound used as an additive, and for example, a compound of the element Me may be appropriately selected for use.
[0064] <Step (2)>
[0065] In step (2), the powdery mixture obtained in step (1) is calcined to produce a calcined material, but it is important to uniformly increase the heat conduction of the entire powdery mixture while suppressing separation of the powdery mixture during calcination to obtain a high-quality positive electrode active material. For this reason, an important feature of the production method according to the present invention lies in the fact that in step (2), the calcined material is produced by calcining the powdery mixture while the powdery mixture is continuously fluidized at least from the start until the end of calcination, in other words, while the powdery mixture is always fluidized.
[0066] Unreacted compounds may remain in the calcined material obtained by means of step (2). Taking into account the fact that calcination may be performed again at a higher temperature after step (2), unreacted compounds may also remain, and the amount thereof depends on the amount of unreacted compounds added and the calcination temperature at which these compounds can react.
[0067] Inhibiting the separation of a powdery mixture containing a precursor compound and a lithium compound means inhibiting the change in the composition of the calcined material caused by the separation of the powdery mixture, that is, inhibiting the change in the ratio (Li / Me) of the amount of lithium (Li) to the total amount of elements (Me) other than lithium and oxygen in the calcined material.
[0068] The calcined material is produced in step (2) while the powdery mixture is continuously fluidized at least from the start to the end of calcination, so that for the calcined materials obtained at all predetermined elapsed times, the coefficient of variation of Li / Me of the calcined material obtained at a predetermined elapsed time (hereinafter also referred to as Li / Me coefficient of variation) is 1.5% or less, preferably 1.3% or less, more preferably 1.2% or less, specifically 1.0% or less.
[0069] The greater the degree to which separation of the powdery mixture during calcination is appropriately suppressed, the greater the similarity of the compositions of N (e.g., N ≥ 10) calcined materials obtained within a predetermined elapsed time, and thus the Li / Me variation coefficient gradually approaches 0%. That is, a smaller Li / Me variation coefficient is preferred, and if it is too large, this is shown by the variation in the composition of the calcined material obtained within a predetermined elapsed time due to separation of the powdery mixture during calcination. In step (2), the powdery mixture is calcined while being continuously fluidized at least from the start of calcination until the end, so that for the calcined materials obtained at all predetermined elapsed times (e.g., at 1 hour, 2 hours, 3 hours, 4 hours, etc.), the Li / Me variation coefficient is 1.5% or less, preferably 1.3% or less, more preferably 1.2% or less, specifically 1.0% or less, and thus the variation in the composition of all calcined materials produced is appropriately suppressed.
[0070] In the present specification, the Li / Me variation coefficient is a value obtained based on the following equation using the standard deviation and average value of Li / Me of N (N=10) samples obtained at random positions from the calcined material obtained at a predetermined elapsed time. In addition, the Li / Me in the calcined material is obtained by heating and dissolving 0.2 g of a sample of the calcined material in 25 mL of a 20% hydrochloric acid solution, and cooling the material, then transferring them to a 100 mL volumetric flask, and introducing pure water (to 100 ml) to prepare a conditioned liquid, and quantitatively determining its elements using a suitable analytical method, such as AES (atomic emission spectrometry), especially ICP-AES (inductively coupled plasma atomic emission spectrometry; synonymous with inductively coupled plasma optical emission spectrometry, abbreviated as ICP-OES) (using, for example, Optima 8300, manufactured by PerkinElmer, Inc.).
[0071] Li / Me variation coefficient (%) = (standard deviation / average value) × 100
[0072] The standard deviation applied here is the sample standard deviation with Bessel correction applied:
[0073]
[0074] in
[0075] s is the (sample) standard deviation
[0076] N is the number of data points in the dataset (here = 10; see above)
[0077] i is a point in the data set (here 1, 2, 3, ..., 10)
[0078] x i is the value of the i-th point in the data set
[0079] is the mean value of the data set
[0080] In step (2), there is no particular limitation on the means for continuously fluidizing the powdery mixture at least from the start until the end of calcination so that the Li / Me variation coefficient is equal to or less than the upper limit value for the calcined material obtained at all predetermined elapsed times, but lifting and stirring may be used to stir the powdery mixture while lifting it.
[0081] In order to fluidize the powdery mixture, the powdery mixture may be simply rotated, for example, but by performing lifting and stirring, the powdery mixture can be calcined in a state of high heat conduction. Lifting and stirring are performed so that the height of the uppermost part of the powdery mixture is preferably between 1.0 and 1.6 times, and more preferably between 1.0 and 1.5 times, of the height of the uppermost part in a state without lifting and stirring, thereby more fully maintaining the state of high heat conduction. If the height of the uppermost part of the powdery mixture is greater than 1.6 times the height of the uppermost part in a state without lifting and stirring, there is a risk of separation due to the difference in specific gravity of the components of the powdery mixture when the lifted powdery mixture falls. There is also a risk of dispersion of the components with a smaller specific gravity due to the force of falling, which again leads to separation of the powdery mixture.
[0082] The particular importance of lifting and stirring is as follows. When the powdery mixture is simply calcined while being fluidized, a portion that is particularly susceptible to heat from the furnace wall and a portion that is not susceptible to the heat are formed in the powdery mixture, and it is thought that this may lead to a decrease in quality. However, when the powdery mixture is lifted and stirred, fluidization also occurs, so that the powdery mixture that has not yet been fluidized near the furnace wall moves upward to the furnace wall, and the powdery mixture is effectively replaced at the furnace wall, whereby a portion that is susceptible to heat from the furnace wall and a portion that is not susceptible to the heat are not formed in the powdery mixture, and calcination can be performed uniformly.
[0083] In order to most effectively calcine the powdered mixture under a high heat conduction state and suppress changes in the composition of the calcined material, it is important that when the powdered mixture is fluidized by means of lifting and stirring, the height of the powdered mixture is not too high relative to the height of the uppermost part of the powdered mixture in a state without lifting and stirring, although this also depends on the possibility of separation of the powdered mixture due to the falling of the powdered mixture.
[0084] In addition, as indicated above, the height of the uppermost portion of the powdered mixture achieved by lifting and stirring is considered to be related to the characteristics of the powdered mixture (i.e., at least the particle size of the precursor compound and the particle size of the lithium compound, the particle size ratio of the two components, and the angle of repose of the powdered mixture, etc.), and the lifting height can be set accordingly according to the characteristics of the powdered mixture supplied for lifting and stirring.
[0085] A rotary kiln in which one or more lifting blades are provided on a surface portion within a furnace tube is preferably used for lifting and stirring, and this makes it easy to continuously produce the calcined material.
[0086] When the heat conduction of a powdered mixture is to be improved by means of lifting and stirring, the extent to which the entire powdered mixture can receive heat is important, for example, when using a rotary kiln in which one or more lifting blades are arranged on a surface portion inside the furnace core tube, the extent to which the entire powdered mixture can contact the surface inside the furnace core tube (hereinafter also referred to as the furnace wall) is important, and this improvement can be achieved, for example, by appropriately adjusting the rotation speed of the rotary kiln and the filling ratio of the powdered mixture in the rotary kiln.
[0087] At the same time, when the powdery mixture is fluidized by means of lifting and stirring, care should be taken not to separate the powdery mixture. For example, when a rotary kiln is used in which one or more lifting blades are provided on a surface portion within the furnace tube, it is considered preferable to appropriately adjust the installation angle of the lifting blades and also appropriately adjust the repose angle of the powdery mixture while taking into account the relationship between the lifting degree of the powdery mixture within the furnace and the dead space caused by the lifting blades.
[0088] When a fixed volume of a powdered mixture is lifted and stirred by means of a rotary kiln in which one or more lifting blades are arranged on a surface portion inside a furnace tube, the powdered mixture can be most efficiently contacted with the furnace wall by installing the lifting blades in a direction parallel to the axial center direction of the furnace tube, but as mentioned above, in view of improving the heat conduction of the powdered mixture while suppressing the separation of the powdered mixture, it is not desirable to determine the installation angle of the lifting blades while only focusing on the efficient contact of the powdered mixture with the furnace wall.
[0089] If the installation angle of one or more lifting blades is too large, in other words, if the one or more lifting blades are too close to the direction parallel to the axial center direction of the furnace tube, there is a risk that the powdery mixture separates and disperses when it is lifted and falls, and this increases the variation of Li / Me of the calcined material. If the installation angle of one or more lifting blades is too small, in other words, if the one or more lifting blades are too close to the direction perpendicular to the axial center direction of the furnace tube, a dead space is formed between the one or more lifting blades and the furnace wall, so that the frequency of contact between the powdery mixture and the furnace wall is reduced, there is a risk that optimal heat transfer will not be achieved, and in view of the repose angle of the powdery mixture, it is impossible to achieve a large lifting amount, and therefore the effect of improving heat conduction provided by lifting and stirring will not be achieved.
[0090] Therefore, when a rotary kiln in which one or more lifting blades are provided on a surface portion inside a furnace tube is used to continuously fluidize a powdery mixture by means of lifting and stirring, the installation angle of the one or more lifting blades is preferably 15° or more, more preferably 20° or less, and 85° or less, more preferably 80° or less, relative to a direction perpendicular to the axial center direction of the furnace tube. Preferably, the installation angle is 15° to 85°, more preferably 20° to 80°, even more preferably 25° to 70°, particularly 25° to 65°, and specifically 30° to 60° relative to a direction perpendicular to the axial center direction of the furnace tube.
[0091] Figure 1 1 is a schematic cross-sectional view in the radial direction showing an example of a furnace tube of a rotary kiln in which lifting blades are provided on a surface portion inside the furnace tube, which furnace tube can be used in an embodiment of the method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention. Figure 1 , a furnace tube 1 of a rotary kiln is provided with a plurality of lifting blades 3 on its surface portion 2, and rotates in the direction of arrow A. The installation angle θ of the lifting blades 3 is an angle relative to a direction perpendicular to the direction of the axial center 4 of the furnace tube 1, and the installation angle θ is preferably adjusted to 15°-85°, as mentioned above.
[0092] It should be noted that there is no particular limitation on the number of lifting blades installed on the surface portion inside the furnace core tube, and the number of lifting blades should be appropriately adjusted according to the diameter of the retort, etc., so as to achieve thorough lifting and stirring. For example, when the retort diameter is about 200 mm-700 mm, it is preferred to install about 3-6 lifting blades, and when the retort diameter is about 1000 mm-2000 mm, it is preferred to install about 4-10 lifting blades.
[0093] The angle of repose of the powdered mixture is also related to the particle size of the powdered mixture, but what is important is that the magnitude of the angle of repose enables the powdered mixture to be lifted to a given height by means of lifting blades arranged on a surface portion within the furnace core tube at a predetermined mounting angle, and its magnitude enables the powdered mixture not to separate when lifted and dropped.
[0094] If the angle of repose of powdered mixture is too large, the powdered mixture is poorly fluidized when lifting and falling, and there is a risk that the powdered mixture supplied to lifting and stirring can not be smoothly replaced. If the angle of repose of powdered mixture is too small, the powdered mixture is fluidized during lifting and falling, and there is a risk that the effect provided by lifting and stirring is reduced. Therefore, the angle of repose of the powdered mixture measured by injection method (according to ISO 902:1976) is preferably 20 ° -80 °. In addition, the particle size of the precursor compound and the particle size of the lithium compound constituting the powdered mixture can be used to determine the angle of repose. Specifically, by appropriately adjusting the particle size of the lithium compound, the expected angle of repose of the powdered mixture can be achieved. The angle of repose in the context of the present invention is relevant to the static angle of repose.
[0095] Here, the lifting height of the powdery mixture will be described by taking as an example the case where the powdery mixture is lifted and stirred by using a rotary kiln in which lifting blades are provided on a surface portion inside a furnace tube.
[0096] Fig. 2 is a schematic cross-sectional view in the radial direction of a furnace tube of a rotary kiln in which lifting blades are provided on a surface portion inside the furnace tube to illustrate the lifting height of a powdery mixture during lifting and stirring using the rotary kiln, which is an example of lifting and stirring in the production method of the present invention, wherein (a) is a schematic cross-sectional view in the radial direction of the furnace tube in which the installation angle of the lifting blades on the surface portion is 45°, and (b) is a schematic cross-sectional view in the radial direction of the furnace tube in which the installation angle of the lifting blades on the surface portion is 60°. When lifting and stirring are performed using such a rotary kiln, the lifting height of the powdery mixture can be set according to the installation angle of the lifting blades.
[0097] As shown in Figures 2(a) and (b), when the powdery mixture is fluidized by the stirring provided by the lifting blades, the repose angle of the powdery mixture is smaller than when there are no lifting blades due to the entry of gas into the powdery mixture, and the height to which the powdery mixture is raised by the rotation of the furnace tube (=the height of the powdery mixture independent of the lifting blades, arrow α) is reduced. In this process, the powdery mixture on the top of the lifting blades is further lifted and falls from the lifting blades when its angle exceeds its own repose angle (arrow β).
[0098] At this time, the height of the powdery mixture independent of the lifting blade (arrow α) is defined as the height of the uppermost part of the powdery mixture in a state without lifting and stirring, and the maximum height of the powdery mixture lifted by the lifting blade (arrow γ) is defined as the height of the uppermost part of the powdery mixture lifted and stirred. The value calculated as the multiplication factor (arrow γ / arrow α) of the height of the uppermost part of the powdery mixture lifted and stirred relative to the height of the uppermost part of the powdery mixture in a state without lifting and stirring is the lifting height of the powdery mixture.
[0099] For example, in the case of Examples 1-2 and 1-3 to be described later, the angle of repose of the powdered mixture 1 is 43.7°, and in Example 1-2 (the installation angle of the lifting blade: 45°, corresponding to Figure 2(a)), the lifting height of the powdered mixture 1 is approximately 1.3 times, and in Example 1-3 (the installation angle of the lifting blade: 60°, corresponding to Figure 2(b)), the lifting height of the powdered mixture 1 is approximately 1.6 times.
[0100] It should be noted that in a rotary kiln in which lifting blades are not provided on the surface portion within the furnace tube, the lifting height of the powdery mixture depends only on the repose angle of the powdery mixture and is higher than the arrow α shown in Figures 2(a) and (b).
[0101] There are no particular restrictions on the conditions under which the powdery mixture is lifted and stirred by means of a rotary kiln in which one or more lifting blades are provided on a surface portion within the furnace tube, but preferably, the following conditions are considered, for example.
[0102] (Retort rotation speed)
[0103] In order to further improve the heat conduction of the powdered mixture, the retort rotation speed should be increased while maintaining the residence time of the powdered mixture in the furnace core tube of the rotary kiln, but if the retort rotation speed is too high, the lithium conversion provided by calcination cannot be fully carried out, and there is a risk of reduced quality of the expected positive active material, and if the retort rotation speed is too low, Li may selectively adhere to the furnace wall, and there is a risk of changes in the composition of the powdered mixture. Therefore, it is preferred to appropriately adjust the optimal retort rotation speed according to the furnace diameter (retort diameter), etc. The technician knows how to adjust the rotation speed to optimize the heat transfer in a specific furnace or can perform a simple preliminary test. For example, when the retort diameter is about 200mm-1500mm, the retort rotation speed can be adjusted to about 0.3rpm-4.0rpm.
[0104] (Powder mixture filling ratio)
[0105] The filling ratio (percentage expressed by the volume of the powdered mixture / the internal capacity of the rotary kiln) of the powdered mixture in the furnace of the rotary kiln can be adjusted by changing the gas input rate and the residence time of the powdered mixture according to the type of the rotary kiln, and the residence time can be adjusted by changing the inclination angle of the retort and the rotation speed of the retort, but if the filling ratio is too high, there is a risk of reducing the quality of the calcined material, and if the filling ratio is too low, there is a risk of insufficient productivity. Therefore, the filling ratio of the powdered mixture is preferably about 3%-30%, and more preferably about 5%-20%.
[0106] (Furnace air velocity and dew point)
[0107] Both the air velocity and the dew point in the furnace can be adjusted by changing the gas input rate. When the gas input rate is low and the dew point is too high, condensation is generated, especially around the inlet of the retort where the powdered mixture is introduced, due to the dissolution of Li from the lithium compound in the powdered mixture, irregular agglomeration / sintering of primary and secondary particles occurs, and there is a risk of reduced quality of the calcined material, while if the gas input rate is high and the air velocity in the furnace is too high, there is a risk of causing selective dispersion (separation) of the powdered mixture. The skilled person knows how to choose an appropriate gas input rate. Preferably, the input gas rate (IGR) corresponds to the output gas rate (OGR; from the raw material) multiplied by a factor a=1-2.5:
[0108] IGR=OGR×a;a=1-2.5.
[0109] (Heating rate)
[0110] The heating rate in relation to the calcined powdered mixture can be adjusted by setting the temperature in the rotary kiln. If the heating rate is too low, there is a risk that insufficient producibility is achieved, whereas if the heating rate is too high, the lithium conversion reaction is insufficient and local lithium conversion reactions occur, so that homogeneity cannot be achieved and there is therefore a risk that the quality of the calcined material is reduced. The skilled person knows how to select an appropriate heating rate for a particular system. Preferably, however, the heating rate is in the range of 200°C / h to 2000°C / h.
[0111] (Surface temperature of furnace core tube)
[0112] If the powdery mixture is lifted and stirred by means of a rotary kiln in which one or more lifting blades are provided on the surface portion within the furnace tube and the powdery mixture is calcined while being continuously fluidized, the maximum temperature of the powdery mixture is too low, there is a risk of reduced quality of the calcined material, and if the maximum temperature is too high, crystal growth proceeds in parallel with the lithium conversion reaction, and there is a risk of reduced quality of the calcined material. In this case, the melting point varies depending on the type of lithium compound constituting the powdery mixture, so that the calcination temperature also varies. For example, when the lithium compound is lithium hydroxide, the temperature setting in the rotary kiln is appropriately adjusted while also taking into account the filling ratio of the powdery mixture, so that the maximum temperature of the powdery mixture is preferably about 500°C-650°C, and more preferably about 530°C-630°C, and the powdery mixture is preferably calcined by setting the surface temperature of the furnace core tube heated by means of a heater to the following temperature: 400°C or greater or 500°C or greater, and 1000°C or less or 850°C or less, that is, preferably 400°C to 1000°C, particularly 500°C to 850°C, more particularly 500°C to 700°C, specifically 550°C to 700°C. More generally, the maximum temperature of the powdery mixture is preferably about 500°C to at most 250°C higher than the melting point of the lithium compound used in step (1), or about 500°C to at most 200°C higher than the melting point of the lithium compound used in step (1), and specifically about 530°C to at most 170°C higher than the melting point of the lithium compound used in step (1), and the powdery mixture is preferably calcined by setting the surface temperature of the furnace core tube heated by means of a heater to 400°C or more or 500°C or more, and 1000°C or less or 850°C or less, that is, preferably 400°C to 1000°C, specifically 500°C to 850°C, more specifically 500°C to 700°C, specifically 550°C to 700°C.
[0113] Independently of the apparatus used in step (2), the powdery mixture obtained in step (1) is preferably heated in step (2) to a temperature of the powdery mixture of 350°C to 950°C, for example, to a temperature of the powdery mixture of 450°C to 800°C, or from 350°C to at most 250°C above the melting point of the lithium compound used in step (1), or from 350°C to at most 200°C above the melting point of the lithium compound used in step (1), or from 450°C to at most 200°C above the melting point of the lithium compound used in step (1), or from 500°C to at most 200°C above the melting point of the lithium compound used in step (1), or from 530°C to at most 170°C above the melting point of the lithium compound used in step (1).
[0114] In step (2), there is no particular limitation on the calcination atmosphere, and it should be an atmosphere in which the lithium conversion reaction and crystal growth proceed reliably and uniformly, and examples of atmospheres that can be used include a decarboxylating oxidizing gas atmosphere having a carbon dioxide concentration of 30 ppm or less, and an oxygen atmosphere having an oxygen concentration of preferably 80 vol% or more and more preferably 90 vol% or more.
[0115] There is no particular limitation on the calcination time, and it should be a time such that the lithium conversion reaction and crystal growth proceed reliably and uniformly, for example, a time of about 1 hour to 12 hours or about 2 hours to 10 hours is preferred.
[0116] <Step (3)>
[0117] As described above, the desired positive electrode active material for a non-aqueous electrolyte secondary battery can be produced by sequentially performing steps (1) and (2), but a step (3) of further calcining the calcined material obtained in step (2) can also be performed in the production method of the present invention. By performing this step (3), more reliable and uniform crystal growth can be achieved, and the quality of the resulting positive electrode active material is further improved.
[0118] In addition, in the production method of the present invention, step (3) as described above may also be performed after the additive is added to the calcined material obtained in step (2). When the additive is added to the calcined material obtained in step (2) in this way, the effect exhibited is different from the effect of adding the additive when the precursor compound is mixed with the lithium compound in step (1), and the improved quality of the resulting positive electrode active material can be envisioned. It should be noted that there is no particular limitation on the additive, and the compound of the element Me or the lithium compound can be appropriately selected for use, and the addition method that can be used includes adding in powder form or spraying in solution form.
[0119] When calcining is performed in step (3), the calcined material is filled in a calcining container such as a sagger or a crucible, and equipment such as a roller kiln can be used, or a rotary kiln can also be used in the same manner as the calcination in step (2). It is preferred to appropriately select equipment that enables fine adjustment of conditions suitable for crystallization for use in the calcination in step (3).
[0120] Also in step (3), there is no particular limitation on the calcining atmosphere, and it should be an atmosphere that allows crystal growth to proceed more reliably and uniformly, and examples of atmospheres that can be used include a decarboxylating oxidizing gas atmosphere having a carbon dioxide concentration of 30 ppm or less, and an oxygen atmosphere having an oxygen concentration of preferably 80 vol% or more and more preferably 90 vol% or more.
[0121] The product of step (2) is usually cooled before being subjected to step (3), but in order to avoid or reduce heat losses and energy consumption, the cooling between these steps can be skipped. If no additives are added before or during step (3), if step (3) is carried out in the same reaction vessel as step (2) and if the calcination atmosphere is not changed, step (3) means extending the reaction time, optionally under a change of temperature.
[0122] The calcination temperature should be appropriately adjusted depending on the maximum temperature of the powdered mixture during calcination in step (2) and the composition of the intended positive electrode active material, but the calcination temperature is preferably adjusted so that the maximum temperature of the calcined material from step (2) is approximately 700°C-1000°C.
[0123] There is no particular limitation on the calcination time, and it should be a time sufficient to obtain a positive electrode active material having a desired crystal structure, for example, a time of about 1 hour to 12 hours or about 2 hours to 10 hours is preferred.
[0124] When the positive electrode active material obtained through the sequence of steps (1) and (2) and step (3) (if necessary) is a high Ni positive electrode active material containing Ni as the element Me and having, for example, a Ni content of 80 mol% or more, there is a possibility that a larger amount of lithium compound (hereinafter referred to as residual Li compound) remains on the particle surface layer compared to a low Ni positive electrode active material having a low Ni content, the residual Li compound being the sum of the lithium compound that did not react during the calcination step and the lithium compound part of the crystal structure that leaves the particle surface layer. The amount of the residual Li compound can be reduced by subjecting the positive electrode active material to a water washing treatment or by surface treating the surface of the primary particles and / or secondary particles of the positive electrode active material.
[0125] In addition, even if the positive electrode active material obtained by the sequence of steps (1) and (2) is a positive electrode active material having a low Ni content, for example, in the case of secondary particles generally composed of primary particles having a small shape, there is a risk of metal elution by hydrogen fluoride due to its large specific surface area, and surface treatment is sometimes required. In addition, even in the case of secondary particles composed of primary particles having a large shape, a so-called sintering promoter such as KOH may be used before calcination in order to achieve a primary particle shape, and a water washing treatment may also be performed in order to wash the sintering promoter.
[0126] There is no particular limitation on the method of surface treatment, and, among others, the following methods can be adopted: while applying a shearing force, alumina fine particles are adhered to the particle surface layer of the positive electrode active material by a dry method, and then heat treatment is performed at about 300°C - 700°C; and the following method: a predetermined amount of the positive electrode active material is introduced into an aqueous solution in which a predetermined amount of sodium sulfate is dissolved, the material is stirred for about 5 minutes - 10 minutes, dehydrated and dried, and then heat treatment is performed at about 250°C - 700°C, whereby the particle surface layer is covered with an aluminum compound. In addition, in addition to the aluminum compound, a boron compound or a tungsten compound can be used in the surface treatment, for example, and the compound can be selected according to the use. In addition, two or more types of compounds can be used at the same time.
[0127] The positive electrode active material for a non-aqueous electrolyte secondary battery produced by the production method according to the present invention may contain a lithium composite oxide containing Li and at least one type of element Me, and there is no particular limitation on its composition, but it preferably has a composition represented by the following formula (I):
[0128] Li a MeO 2 (I)
[0129] (In this formula, Me is an element other than Li and O, and 0.95 ≤ a ≤ 1.40).
[0130] In the positive electrode active material having the composition represented by the above formula (I), the amount a of Li, in other words, the ratio (Li / Me) of the amount of Li to the total amount of the element Me is preferably 0.95 ≤ a ≤ 1.40, more preferably 0.95 ≤ a ≤ 1.25, and particularly preferably 0.96 ≤ a ≤ 1.15. Similarly independent of formula (I), in the positive electrode active material, the ratio (Li / Me) of the amount of Li to the total amount of the element Me is preferably 0.95 ≤ a ≤ 1.40, more preferably 0.95 ≤ a ≤ 1.25, and particularly preferably 0.96 ≤ a ≤ 1.15.
[0131] In the positive electrode active material having the composition represented by the above formula (I), Me is preferably at least Ni, and more preferably at least Ni, Co, and Al and / or Mn. When Me is at least Ni, the amount of Ni, in other words, the ratio (Ni / Me) of the amount of Ni to the total amount of the element Me is preferably 0.3 < b ≤ 1, more preferably 0.5 < b < 1, and particularly preferably 0.8 < b < 1. Similarly independent of formula (I), if the positive electrode active material contains Ni, the ratio (Ni / Me) of the amount of Ni to the total amount of one or more other elements Me is preferably 0.3 < b ≤ 1, more preferably 0.5 < b < 1, and particularly preferably 0.8 < b < 1.
[0132] The properties of the positive electrode active material for non-aqueous electrolyte secondary batteries produced by the production method according to the present invention vary mainly depending on its composition, and therefore they cannot be precisely specified, but the average particle size of the secondary particles (average secondary particle size) and the average crystallite size are preferably values within the range indicated below, for example.
[0133] The average secondary particle size varies depending on the intended use of the positive electrode active material, but it can be determined while considering characteristics including increased capacity due to higher filling characteristics and high cycle characteristics, and the average secondary particle size is, for example, preferably about 1μm-30μm, and more preferably about 2μm-25μm.
[0134] The crystallite size can be adjusted by means of the desired composition and the primary and secondary particle sizes, and is preferably about 50 nm to 600 nm, and more preferably about 60 nm to 500 nm.
[0135] In this specification, the secondary particle size is a value obtained based on an electron microscope photograph (SEM photograph) of secondary particles of a positive electrode active material image, particularly based on an SEM photograph using a scanning electron microscope SEM-EDS [field emission scanning electron microscope JSM-7100F: manufactured by JEOL Ltd] at an accelerating voltage of 10 kV. Here, the scale shown in the electron microscope photograph is used as a reference scale.
[0136] In this specification, the crystallite size is a value determined by obtaining XRD diffraction data of a positive electrode active material, specifically, obtaining XRD diffraction data by the following method and then performing Rietveld analysis.
[0137] The XRD diffraction data of the positive electrode active material were obtained using an X-ray diffraction apparatus [SmartLab, manufactured by Rigaku Corp., Japan] under the following X-ray diffraction conditions, and then the XRD diffraction data were used to perform Rietveld analysis, referring to "RA Young, ed., "The Rietveld Method", Oxford University Press (1992)".
[0138] (X-ray diffraction conditions)
[0139] Radiation source: Cu-Kα
[0140] Accelerating voltage and current: 45 kV and 200 mA
[0141] Sampling width: 0.02 degrees
[0142] Scan width: 15 degrees - 122 degrees
[0143] Scanning speed: 1.0 step / second
[0144] Divergent slit: 2 / 3 degree
[0145] Receiving slit width: 0.15 mm
[0146] Scattering slit: 2 / 3 degree
[0147] The positive electrode active material for a non-aqueous electrolyte secondary battery produced by the production method according to the present invention can be included in the positive electrode of the non-aqueous electrolyte secondary battery, and the non-aqueous electrolyte secondary battery includes the positive electrode, a negative electrode, and an electrolytic solution containing an electrolyte.
[0148] When producing the positive electrode, a conductive agent and a binder are mixed with the positive electrode active material by means of a common method. For example, acetylene black, carbon black, graphite, etc. are preferred as the conductive agent. For example, polytetrafluoroethylene and polyvinylidene fluoride, etc. are preferred as the binder.
[0149] For the negative electrode, not only negative electrode active materials such as lithium metal, graphite, and low-crystallinity carbon materials can be used, but also at least one non-metal or metal element selected from the group consisting of Si, Al, Sn, Pb, Zn, Bi, and Cd, or an alloy containing them, or a chalcogenide containing them can be used.
[0150] Examples of solvents of the electrolytic solution that can be used include organic solvents, which include at least one type of carbonate such as ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate, or at least one type of ether such as dimethoxyethane.
[0151] In addition to lithium hexafluorophosphate (LiPF 6 ), at least one type of lithium salt such as lithium perchlorate or lithium tetrafluoroborate can be dissolved in the solvent and used.
[0152] <Function>
[0153] By virtue of the production method of the present invention, a positive electrode active material for a non-aqueous electrolyte secondary battery can be manufactured with good production efficiency, and the positive electrode active material can endow the non-aqueous electrolyte secondary battery with excellent battery characteristics without any quality degradation.
[0154] [Examples]
[0155] Representative examples and comparative examples of the present invention will be given below to describe the present invention in specific terms, but the present invention is not limited to these examples. It should be noted that the characteristics and the methods for obtaining these characteristics, etc. are given as follows.
[0156] <XRD Diffraction>
[0157] The XRD diffraction data of the positive electrode active material were obtained using an X-ray diffraction apparatus [SmartLab, manufactured by Rigaku Corp., Japan] under the following X-ray diffraction conditions, and then the XRD diffraction data were used to perform Rietveld analysis, referring to "RA Young, ed., "The Rietveld Method", Oxford University Press (1992)".
[0158] (X-ray diffraction conditions)
[0159] Radiation source: Cu-Kα
[0160] Accelerating voltage and current: 45 kV and 200 mA
[0161] Sampling width: 0.02 degrees
[0162] Scan width: 15 degrees - 122 degrees
[0163] Scan speed: 1.0 step / second
[0164] Divergence slit: 2 / 3 degree
[0165] Receiving slit width: 0.15mm
[0166] Scattering slit: 2 / 3 degree
[0167] <Composition of Precursor Compound and Calcined Material (Positive Electrode Active Material)>
[0168] 0.2 g of samples of the precursor compound and the calcined material (positive electrode active material) were each heated and dissolved in 25 mL of a 20% hydrochloric acid solution, and the material was cooled and then transferred to a 100 mL volumetric flask, and pure water (added to 100 ml) was introduced to prepare an adjusted liquid, and its elements were quantitatively determined using ICP-AES (Optima 8300, produced by PerkinElmer, Inc.).
[0169] <Button cell using positive electrode active material>
[0170] A 2032-type button cell using a positive electrode active material is produced by using a positive electrode, a negative electrode, and an electrolyte produced by the following corresponding methods.
[0171] (positive electrode)
[0172] Acetylene black and graphite were used as conductive agents, the weight ratio of acetylene black: graphite = 1: 1, and polyvinylidene fluoride was used as a binder, the positive electrode active material, the conductive agent and the binder were mixed to achieve a weight ratio of positive electrode active material: conductive agent: binder = 90: 6: 4, and the slurry obtained by mixing these materials with N-methylpyrrolidone was coated on an aluminum foil. The coated aluminum foil was dried at 110° C. to prepare a sheet, which was punched to a diameter of 15 mm and then wound so that the density of the composite material was 3.0 g / cm 3 , and use it as the positive electrode.
[0173] (negative electrode)
[0174] A lithium foil having a thickness of 500 μm punched out to a diameter of 16 mm was used as the negative electrode.
[0175] (Electrolyte)
[0176] A mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) was prepared at a volume ratio of EC:DMC=1:2, and 1 M LiPF 6 A solution obtained by mixing the electrolyte with the solvent is used as an electrolytic solution.
[0177] <Battery Characteristics of Non-aqueous Electrolyte Secondary Batteries>
[0178] (Initial charge capacity and initial charge / discharge efficiency)
[0179] The button cell produced by the above method was charged at 25°C at a current density of 18 mA / g to 4.30 V (upper limit voltage), and then charged at a constant voltage until the current reached 2 mA / g. The capacity at this time was taken as the initial charge capacity (mAh / g).
[0180] After a 5-minute pause, constant current discharge was performed to 3.00 V at a current density of 18 mA / g under the same environment, and the initial discharge capacity (mAh / g) was measured after a 5-minute pause. It should be noted that according to condition A, a series of steps until the initial discharge capacity was measured was regarded as a charge / discharge cycle.
[0181] The initial charge / discharge efficiency was calculated based on the following formula using the measured value of the initial charge capacity and the measured value of the initial discharge capacity.
[0182] Initial charge / discharge efficiency (%) = (initial discharge capacity / initial charge capacity) × 100
[0183] <Synthesis Example 1: Synthesis of Precursor Compound 1>
[0184] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and an aluminum sulfate aqueous solution were mixed so that the ratio (molar ratio) of Ni, Co and Al was Ni:Co:Al=89:7:4, and a mixed aqueous solution was obtained. 10 L of pure water to which 300 g of sodium hydroxide aqueous solution and 500 g of ammonia water had been added was prepared in advance in a reaction tank as a mother liquor, a nitrogen atmosphere was set in the reaction tank with the aid of nitrogen at a flow rate of 0.7 L / min, and the reaction was also carried out under a nitrogen atmosphere.
[0185] Thereafter, while the stirring blade was rotated at 1000 rpm, the mixed aqueous solution, the sodium hydroxide aqueous solution and the ammonia water were simultaneously added dropwise at a predetermined rate, and by means of a crystallization reaction, wherein the amount of the alkaline solution added was adjusted to reach pH 11.8, Ni, Co and Al were crystallized and co-precipitated to form agglomerated particles, and a co-precipitate was obtained.
[0186] Thereafter, the slurry in the reactor was subjected to solid-liquid separation and further washed with pure water to reduce residual impurities, and then the coprecipitate in an agglomerated state was dried at 110° C. for 12 hours under an ambient air atmosphere to obtain Precursor Compound 1. At this time, D50 in the volume-based particle size distribution of Precursor Compound 1 was 11.2 μm.
[0187] <Synthesis Example 2: Synthesis of Precursor Compound 2>
[0188] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution were mixed so that the ratio (molar ratio) of Ni, Co and Mn was Ni:Co:Mn=5:2:3, and a mixed aqueous solution was obtained. 10 L of pure water to which 300 g of sodium hydroxide aqueous solution and 500 g of ammonia water had been added was prepared in advance in a reaction tank as a mother liquor, a nitrogen atmosphere was set in the reaction tank with the aid of nitrogen at a flow rate of 0.7 L / min, and the reaction was also carried out under a nitrogen atmosphere.
[0189] Thereafter, while the stirring blade was rotated at 1000 rpm, the mixed aqueous solution, the sodium hydroxide aqueous solution and the ammonia water were simultaneously added dropwise at a predetermined rate, and by means of a crystallization reaction, wherein the amount of the alkaline solution added was adjusted to reach pH 12.0, Ni, Co and Mn were crystallized and co-precipitated to form agglomerated particles, and a co-precipitate was obtained.
[0190] Thereafter, the slurry in the reactor was subjected to solid-liquid separation and further washed with pure water to reduce residual impurities, and then the coprecipitate in an agglomerated state was dried at 110° C. for 12 hours under an ambient air atmosphere to obtain Precursor Compound 2. At this time, D50 in the volume-based particle size distribution of Precursor Compound 2 was 5.1 μm.
[0191] <Example 1-1: Production of positive electrode active material>
[0192] Precursor compound 1 and anhydrous lithium hydroxide were weighed so that the ratio (molar ratio) of Li to the total amount of Ni, Co and Al was Li / (Ni+Co+Al)=1.02, and these materials were mixed using a mixer to prepare a powdered mixture 1. The angle of repose of the powdered mixture 1 measured by an injection method was 43.7°.
[0193] Using a rotary kiln having a retort diameter of 300 mm and having four lifting blades circumferentially arranged on a surface portion within the furnace tube at an installation angle of 30°, as shown in FIG. 3( a), the powdery mixture 1 was calcined in an oxygen atmosphere (oxygen concentration: 97 vol%) under the following conditions for a period of 13 hours while being continuously fluidized by lifting and stirring (the powdery mixture 1 flows as indicated by arrow B), and a powdery calcined material was continuously produced. It should be noted that at the time of calcination, the powdery mixture 1 was introduced into the rotary kiln and the time for calcining the powdery mixture 1 was set to 4 hours after the powdery mixture was stably and continuously discharged, and the time for calcining the powdery mixture 1 at the highest temperature (about 600° C., as indicated below) was about 4 hours.
[0194] In addition, the lifting and stirring provided by the lifting blades are performed so that the height of the uppermost portion of the powdered mixture 1 is about 1.0 times the height of the uppermost portion in a state without lifting and stirring. In addition, the size of the lifting blades is set so that 50% of the total amount of the powdered mixture 1 can be stirred in the next rotation at a filling ratio of 20%.
[0195] (Rotary kiln conditions)
[0196] Rotation speed of retort: 0.9rpm
[0197] Filling ratio: 20%
[0198] Air velocity and dew point in the furnace: The gas input rate is adjusted to 47L / min
[0199] Heating rate: The surface temperature of the furnace tube is set as indicated below.
[0200] The maximum surface temperature of the furnace tube: 640℃
[0201] Maximum temperature of powdered mixture 1: about 600°C
[0202] During the calcination of the powdered mixture 1 over a period of 13 hours, a time of 4 hours from the start of calcination after stable emission was achieved was taken as an initial time, and 10 samples were randomly selected from the fired materials obtained after each hour from the initial time, and the Li / Me of each sample was identified, and the Li / Me variation coefficient at each elapsed time was calculated from the standard deviation and the average value according to the method described above.
[0203] Then 8 kg of the obtained powdered calcined material was filled in a sagger having a width of 300 mm and a depth of 100 mm, and calcined for a period of 4 hours in an oxygen atmosphere (oxygen concentration: 97 vol%) using a rotary bed kiln so that the maximum temperature of the powdered calcined material was approximately 740°C, and a positive electrode active material was obtained.
[0204] The average secondary particle size and crystallite size of the resulting positive electrode active material were obtained according to the methods described above.
[0205] <Example 1-2: Production of positive electrode active material>
[0206] The positive electrode active material was obtained in the same manner as in Example 1-1, except that the rotary kiln of Example 1-1 was changed to a rotary kiln having four lifting blades circumferentially arranged on the surface portion inside the furnace core tube at an installation angle of 45°, as shown in FIG. 3( b) (the powdery mixture 1 flows as shown by arrow B), and the lifting and stirring provided by the lifting blades were performed so that the height of the uppermost portion of the powdery mixture 1 was about 1.3 times the height of the uppermost portion in the state without lifting and stirring. In addition, the Li / Me variation coefficient at each elapsed time, and the average secondary particle size and crystallite size of the positive electrode active material were also obtained in the same manner as in Example 1-1.
[0207] <Example 1-3: Production of positive electrode active material>
[0208] The positive electrode active material was obtained in the same manner as in Example 1-1, except that the rotary kiln of Example 1-1 was changed to a rotary kiln having four lifting blades circumferentially arranged on the surface portion inside the furnace core tube at an installation angle of 60°, as shown in FIG. 3(c) (the powdered mixture 1 flows as shown by arrow B), and the lifting and stirring provided by the lifting blades were performed so that the height of the uppermost portion of the powdered mixture 1 was about 1.6 times the height of the uppermost portion in the state without lifting and stirring. In addition, the Li / Me variation coefficient at each elapsed time, and the average secondary particle size and crystallite size of the positive electrode active material were also obtained in the same manner as in Example 1-1.
[0209] <Comparative Example 1-1: Production of positive electrode active material>
[0210] The positive electrode active material was obtained by preparing 10 sheaths in which 8 kg of the powdered mixture 1 prepared in the same manner as in Example 1-1 was filled into a sagger having a width of 300 mm and a depth of 100 mm, and calcining the material for 4 hours in an oxygen atmosphere (oxygen concentration: 97 vol%) using a rotary bed kiln so that the maximum temperature of the powdered material 1 was about 740° C. The positive electrode active material obtained in each sheath was ground, 10 samples were obtained at random, and the Li / Me variation coefficient, and the average secondary particle size and crystallite size of the positive electrode active material were obtained in the same manner as in Example 1-1.
[0211] <Example 2-1: Production of positive electrode active material>
[0212] Precursor compound 2 and anhydrous lithium hydroxide were weighed so that the ratio (molar ratio) of Li to the total amount of Ni, Co and Mn was Li / (Ni+Co+Mn)=1.125, and these materials were mixed using a mixer to prepare a powdered mixture 2. The angle of repose of the powdered mixture 2 measured by the injection method was 56.3°.
[0213] Using a rotary kiln having a retort diameter of 300 mm and having four lifting blades circumferentially arranged on a surface portion within the furnace tube at an installation angle of 30°, as shown in FIG. 3( a), the powdery mixture 2 was calcined in an oxygen atmosphere (oxygen concentration: 97 vol%) under the following conditions for a period of 13 hours while being continuously fluidized by lifting and stirring (the powdery mixture 2 flowed as indicated by arrow B), and a powdery calcined material was continuously produced. It should be noted that at the time of calcination, the powdery mixture 2 was introduced into the rotary kiln and the time for calcining the powdery mixture 2 was set to 4 hours after the powdery mixture was stably and continuously discharged, and the time for calcining the powdery mixture 2 at the highest temperature (about 560° C., as indicated below) was about 4 hours.
[0214] In addition, the lifting and stirring provided by the lifting blades are performed so that the height of the uppermost portion of the powdery mixture 2 is about 1.0 times the height of the uppermost portion in a state without lifting and stirring. In addition, the size of the lifting blades is set so that 50% of the total amount of the powdery mixture 2 can be stirred in one rotation at a filling ratio of 20%.
[0215] (Rotary kiln conditions)
[0216] Rotation speed of retort: 1.1rpm
[0217] Filling ratio: 20%
[0218] Air velocity and dew point in the furnace: The gas input rate is adjusted to 54L / min
[0219] Heating rate: The surface temperature of the furnace tube is set as indicated below.
[0220] The maximum surface temperature of the furnace tube: 630℃
[0221] Maximum temperature of powdered mixture 2: about 560°C
[0222] During the calcination of the powdered mixture 2 over a period of 13 hours, a time of 4 hours from the start of calcination after stable emission was achieved was taken as an initial time, and 10 samples were randomly selected from the fired materials obtained after each hour from the initial time, and the Li / Me of each was identified, and the Li / Me variation coefficient at each elapsed time was calculated from the standard deviation and the average value according to the method described above.
[0223] Then 8 kg of the obtained powdered calcined material was filled in a sagger having a width of 300 mm and a depth of 100 mm, and calcined for a period of 4 hours in an oxygen atmosphere (oxygen concentration: 97 vol%) using a rotary bed kiln so that the maximum temperature of the powdered calcined material was approximately 940°C, and a positive electrode active material was obtained.
[0224] The average secondary particle size and crystallite size of the resulting positive electrode active material were obtained according to the methods described above.
[0225] <Example 2-2: Production of positive electrode active material>
[0226] The positive electrode active material was obtained in the same manner as in Example 2-1, except that the rotary kiln of Example 2-1 was changed to a rotary kiln having four lifting blades circumferentially arranged on the surface portion inside the furnace tube at an installation angle of 45°, as shown in FIG. 3( b) (the powdery mixture 2 flows as shown by arrow B), and the lifting and stirring provided by the lifting blades were performed so that the height of the uppermost portion of the powdery mixture 2 was about 1.4 times the height of the uppermost portion in the state without lifting and stirring. In addition, the Li / Me variation coefficient at each elapsed time, and the average secondary particle size and crystallite size of the positive electrode active material were also obtained in the same manner as in Example 2-1.
[0227] <Example 2-3: Production of positive electrode active material>
[0228] The positive electrode active material was obtained in the same manner as in Example 2-1, except that the rotary kiln of Example 2-1 was changed to a rotary kiln having four lifting blades circumferentially arranged on the surface portion inside the furnace tube at an installation angle of 60°, as shown in FIG. 3(c) (the powdery mixture 2 flows as indicated by arrow B), and the lifting and stirring provided by the lifting blades were performed so that the height of the uppermost portion of the powdery mixture 2 was about 1.7 times the height of the uppermost portion in the state without lifting and stirring. In addition, the Li / Me variation coefficient at each elapsed time, and the average secondary particle size and crystallite size of the positive electrode active material were also obtained in the same manner as in Example 2-1.
[0229] <Comparative Example 2-1: Production of positive electrode active material>
[0230] The positive electrode active material was obtained by preparing 10 claddings in which 8 kg of the powdered mixture 2 prepared in the same manner as in Example 2-1 was filled into a sagger having a width of 300 mm and a depth of 100 mm, and calcining the material for 4 hours in an oxygen atmosphere (oxygen concentration: 97 vol%) using a rotary bed kiln so that the maximum temperature of the powdered material 2 was about 940° C. The positive electrode active material obtained in each cladding was ground, 10 samples were obtained at random, and the Li / Me variation coefficient, and the average secondary particle size and crystallite size of the positive electrode active material were obtained in the same manner as in Example 2-1.
[0231] The Li / Me variation coefficient at each elapsed time determined for the positive electrode active materials obtained in Examples 1-1 to 1-3 and Comparative Example 1-1, and in Examples 2-1 to 2-3 and Comparative Example 2-1 is shown in Table 1, and the average secondary particle size and crystallite size of the positive electrode active materials are shown in Table 2.
[0232] In addition, the initial charge capacity and initial charge / discharge efficiency were obtained as battery characteristics of a nonaqueous electrolyte secondary battery using the positive electrode active materials obtained in Examples 1-1 to 1-3 and Comparative Example 1-1, and in Examples 2-1 to 2-3 and Comparative Example 2-1 in the positive electrode thereof according to the method described above. The results are shown in Table 2.
[0233] [Table 1]
[0234]
[0235] [Table 2]
[0236]
[0237] In Examples 1-1 to 1-3 and Examples 2-1 to 2-3 of the production method according to the present invention, there is no separation of the powdered mixture containing the precursor compound and the lithium compound, heat conduction is sufficiently increased, and the powdered mixture is continuously calcined while being fluidized from the beginning to the end, so that for the calcined materials obtained at all predetermined elapsed times (calcined materials obtained after each lapse of one hour), the Li / Me variation coefficient is 1.5% or less, and it is therefore obvious that the non-aqueous electrolyte secondary battery using the positive electrode active material obtained in these examples has a favorable initial charge capacity and initial charge / discharge efficiency.
[0238] On the other hand, in Comparative Example 1-1 and Comparative Example 2-1, the powdered mixture is not calcined while being continuously fluidized from the beginning to the end so that the Li / Me variation coefficient of the obtained calcined material is 1.5% or less, and therefore the primary particles and the secondary particles formed by agglomerated primary particles do not have a uniform shape, changes in crystallinity occur, and the agglomerates of the secondary particles are unevenly distributed in the formed powder, so it is obvious that a reduction in battery characteristics can be seen in the non-aqueous electrolyte secondary battery using the positive electrode active material obtained in these comparative examples.
[0239] [Industrial Applicability]
[0240] The positive electrode active material obtained by means of the production method according to the present invention can impart excellent battery characteristics to a nonaqueous electrolyte secondary battery without any quality degradation.
[0241] [Explanation of symbols]
[0242] 1 Furnace core tube
[0243] 2 Surface part
[0244] 3 Lifting blades
[0245] 4 Axial center
[0246] θ Installation angle
Claims
1. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, the method comprising at least the following steps in sequence: (1) Step (1), wherein at least a positive electrode active material precursor compound and a lithium compound are mixed to prepare a powdery mixture; and (2) step (2), wherein the powdery mixture obtained in step (1) is calcined to produce a calcined material, wherein the precursor compound is a composite compound containing oxygen (O) and at least one element (Me) other than lithium (Li) and oxygen (O), and Wherein in step (2), the calcined material is produced while the powdery mixture is continuously fluidized at least from the beginning to the end of calcination, so that for the calcined materials obtained at all predetermined elapsed times, the coefficient of variation of the ratio (Li / Me) of the amount of lithium (Li) to the total amount of element (Me) in the calcined material obtained at a predetermined elapsed time is 1.5% or less.
2. The method of claim 1, wherein: The means for continuously fluidizing the powdery mixture at least from the beginning to the end of calcination are lifting and stirring, for stirring the powdery mixture while lifting it.
3. The method of claim 2, wherein: With the lifting and stirring, the height of the uppermost portion of the powdery mixture is 1.0 to 1.6 times the height of the uppermost portion in a state without the lifting and stirring.
4. The method according to any one of claims 2 or 3, wherein: The calcined material is continuously produced by using a rotary kiln in which one or more lifting blades are provided on a surface portion inside a furnace tube to perform the lifting and stirring.
5. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, the method comprising at least the following steps in sequence: (1) Step (1), wherein at least a positive electrode active material precursor compound and a lithium compound are mixed to prepare a powdery mixture; and (2) step (2), wherein the powdery mixture obtained in step (1) is calcined to produce a calcined material, wherein the precursor compound is a composite compound containing oxygen (O) and at least one element (Me) other than lithium (Li) and oxygen (O), and wherein in step (2), the calcined material is produced while the powdered mixture is continuously fluidized at least from the beginning to the end of calcination; wherein step (2) is carried out in a rotary kiln in which one or more lifting blades are arranged on a surface portion inside the furnace core tube.
6. The method according to any one of claims 4 and 5, wherein: The one or more lifting blades are installed at an angle of 15° to 85°, preferably 20° to 80°, relative to a direction perpendicular to the axial center direction of the furnace core tube in the rotary kiln.
7. The method of claim 6, wherein: The one or more lifting blades are installed at an angle of 25° to 70°, preferably 25° to 65°, relative to a direction perpendicular to the axial center direction of the furnace core tube in the rotary kiln.
8. The method of claim 7, wherein: The one or more lifting blades are installed at an angle of 30° to 60° in the rotary kiln relative to a direction perpendicular to the axial center direction of the furnace core tube.
9. The method according to any one of the preceding claims, wherein in step (2), the powdery mixture obtained in step (1) is heated to a temperature of 350°C to 1000°C, preferably 350°C to a maximum of 250°C above the melting point of the lithium compound used in step (1).
10. The method according to any one of claims 4 to 9, wherein: The powdery mixture is calcined while setting the surface temperature of the hearth tube to 400°C to 1000°C.
11. A method as claimed in any one of the preceding claims, wherein: Me in the precursor compound containing oxygen (O) and at least one element (Me) includes at least one of the following: nickel (Ni), cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), niobium (Nb), tungsten (W), molybdenum (Mo), vanadium (V), chromium (Cr), calcium (Ca), iron (Fe), gallium (Ga), strontium (Sr), yttrium (Y), ruthenium (Ru), indium (In), tin (Sn), tantalum (Ta), bismuth (Bi), zirconium (Zr), boron (B) and / or phosphorus (P); wherein Me preferably includes at least one of the following: nickel (Ni), cobalt (Co), manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), niobium (Nb), or tungsten (W).
12. A method as claimed in any one of the preceding claims, wherein: The precursor compound containing oxygen (O) and at least one element (Me) is a composite hydroxide, composite oxide, composite carbonate or a mixed form thereof.
13. The method according to any one of claims 11 or 12, wherein: Me includes Ni; wherein Me preferably includes Ni, Co, and one or two of Al and Mn.
14. The method of claim 13, wherein: The molar ratio b of Ni to the total amount of other Me is in the range of 0.3 < b ≤ 1, preferably in the range of 0.5 < b < 1.
15. A method as claimed in any one of the preceding claims, wherein: The lithium compound is selected from the group consisting of lithium carbonate, lithium hydroxide (e.g., in the form of anhydrous LiOH or LiOH monohydrate), lithium nitrate, lithium acetate, lithium bromide, lithium chloride, lithium citrate, lithium fluoride, lithium iodide, lithium lactate, lithium oxalate, lithium phosphate, lithium pyruvate, lithium sulfate, lithium oxide, and mixtures thereof.
16. The method of claim 15, wherein: The lithium compound is selected from the group consisting of lithium carbonate, lithium hydroxide (e.g., in the form of anhydrous LiOH or LiOH monohydrate), and mixtures thereof.
17. A method as claimed in any one of the preceding claims, wherein: The precursor compound and the lithium compound are used in step (1) in such amounts that the ratio a (Li / Me) of the amount of Li to the total amount of the element Me is in the range of 0.95 ≤ a ≤ 1.40, preferably in the range of 0.95 ≤ a ≤ 1.25, and more preferably in the range of 0.96 ≤ a ≤ 1.15.
Citation Information
Patent Citations
Rotary kiln
JP4670861B2